A Numerical Computation of Water Quality Measurement in a Uniform Channel Using a Finite Difference Method - Nopparat Pochai; Rujira Deepana (My University, 2011)
Water pollution assessment problems arise frequently in environmental science. In this research, a finite difference method for solving a one-dimensional steady convection-diffusion equation with variable coefficients is presented.
Keywords: Finite difference; Soil, Finite Element Methods